Changing beliefs in the bayou city - Grove, Lauren; Lynn, Virginia (Frontiers in Future Transportation, 2022)
Vision Zero has been changing traffic safety culture internationally since the 1990s, but in Houston, Texas it did not kick off until the 2010s. Houston presents challenges in scale and development patterns, which make for a slow, deliberate process when furthering a transportation paradigm shift towards zero traffic deaths. Bringing in leaders who champion and own Vision Zero has been key, and a traffic safety culture shift is happening at necessary places inside the City of Houston organization. However, transforming community-wide beliefs in a city like Houston requires meaningful engagement, clear strategies and sustained political will. City of Houston officials, stakeholders and residents are working to meet these challenges. This article will delve into the effort that has been made to change Houston’s transportation culture and the dire need for street safety improvements.